Criminological Analysis of the Crimes of Fraud and Embezzlement with Perpetrators Using False Identities Through Social Media - Arif Munandar (LEGAL BRIEF, 2019)
Crime of fraud and embezzlement with perpetrators using fake identities in the police station Salatiga from 2016-2018 there were 413 cases. Based on this, the author makes a thesis entitled Criminological Analysis of Fraud and Darkness Crime with Actors Using False Identities through Social Media. The problem sinthi sstudyare: (1) What are the factors that cause fraud and embezzlement with perpetrators using fake identities through social media? (2) How are efforts to overcome fraud and embezzlement crimes against perpetrators using false identities through social media? This study uses a normative juridical approach and an empirical juridical approach. The results of the study and discussion show: the causes of fraud and embezzlement with the perpetrators of using false identities through social media include internal factors namely educational and trial factors and external factors namely economic factors, environmental factors, global development factors and law enforcement factors. Mitigation can be done with a pre-emptive effort, namely by providing employment. Preventive countermeasures or actions taken to prevent fraud and embezzlement by holding legal counseling, prevention, approaches, friends programs, social media and door to door systems. Repressive efforts are by imposing a punitive sentence against the perpetrators of fraud and embezzlement in accordance with Article 378 and Article 372 of the Criminal Code, namely a maximum of 4 years in prison. Suggestions in this study are: (1) The community is advised to increase alertness to anyone by not easily believing in all kinds of persuasion or forms of cooperation invitation or whatever. (2) The police are advised to be more active in educating the public.